The reversibility of cardiac damage after transcatheter aortic valve implantation and short-term outcomes in a real-world setting - Myagmardorj, Rinchyenkhand; Fortuni, Federico; Genereux, Philippe; Nabeta, Takeru; Stassen, Jan; Galloo, Xavier; Meucci, Maria Chiara; Butcher, Steele; van der Kley; Frank; Cohen, David J.; Clavel, Marie-Annick; et al. (Oxford University Press (OUP), 2025)
Aims
This study aims to assess the changes in cardiac damage stage in a real-world cohort of patients undergoing transcatheter aortic valve implantation (TAVI), and to investigate the prognostic value of cardiac damage stage evolution.
Methods and results
Patients with severe aortic stenosis (AS) undergoing TAVI were retrospectively analysed. A five-stage system based on the presence and extent of cardiac damage assessed by echocardiography was applied before and 6 months after TAVI. Multivariable Cox regression analyses were used to examine independent prognostic value of the changes in cardiac damage after TAVI. A total of 734 patients with severe AS (mean age, 79.8 ± 7.4 years; 55% male) were included. Before TAVI, 32 (4%) patients did not show any sign of extra-valvular cardiac damage (Stage 0), 85 (12%) had left ventricular damage (Stage 1), 220 (30%) left atrial and/or mitral valve damage (Stage 2), 227 (31%) pulmonary vasculature and/or tricuspid valve damage (Stage 3), and 170 (23%) right ventricular damage (Stage 4). Six months after TAVI, 39% of the patients improved at least one stage in cardiac damage. Staging of cardiac damage at 6 months after TAVI [hazard ratio (HR) per one-stage increase, 1.391; P = 0.035] as well as worsening in the stage of cardiac damage (HR, 3.729; P = 0.005) were independently associated with 2-year all-cause mortality.
Conclusion
More than one-third of patients with severe AS showed an improvement in cardiac damage 6 months after TAVI. Staging cardiac damage at baseline and follow-up may improve risk stratification in patients undergoing TAVI.